Association of HIV infection with Incident Diabetes Mellitus: Impact of using Hemoglobin A1C as a Criterion for Diabetes - Tien, Phyllis C (2012)
BACKGROUND: Data regarding the association between HIV and DM are conflicting, with little known regarding the impact of including hemoglobin A1C (A1C) as a criterion for DM. METHODS: Pooled logistic regression was used to quantify the association between HIV and DM in 1501 HIV-infected and 550 HIV-uninfected participants from the Women’s Interagency HIV Study. Incident DM was defined using three DM definitions: (I) fasting glucose (FG) ≥126mg/dl, anti-DM medication, or reporting DM diagnosis (with confirmation by FG≥126mg/dl or anti-DM medication); (II) confirmation with a second FG≥126mg/dl; and (III) addition of A1C≥6.5% confirmed by FG≥126mg/dl or anti-DM medication. RESULTS: DM incidence per 100 person-years was 2.44, 1.55, and 1.70 for HIV-infected women; 1.89, 0.85, and 1.13 for HIV-uninfected women, using definition I, II, and III, respectively. After adjustment for traditional DM risk factors, HIV infection was associated with 1.23, 1.90, and 1.38-fold higher risk of incident DM, respectively; the association reached statistical significance only when confirmation with a second FG≥126mg/dl was required. Older age, obesity, and a family history of DM were each consistently and strongly associated with increased DM risk. CONCLUSIONS: HIV infection is consistently associated with greater risk of DM. Inclusion of an elevated A1C to define DM increases the accuracy of the diagnosis and only slightly attenuates the magnitude of the association otherwise observed between HIV and DM. By contrast, a DM diagnosis made without any confirmatory criteria for FG ≥126mg/dl overestimates the incidence, while also underestimating the effects of HIV on DM risk, and should be avoided.